Riskc: bridging microcontroller operanting systems and architectures (2011)
One of the challenges in developing software for use in embedded systems is the limited hardware resources. This challenge can be significantly increased if the system uses custom or special-purpose processors. As system complexity increases and timing requirements become more strict the use of an Operating Systems (OS) on top of which system application is built is becoming a common practice. OSs are high coupled to the hardware requiring that they are ported to adequately match the processor's architecture, which can become a time-consuming and costly task when custom or special-purpose processors are used. This work presents an automated code generation tool, based on model-driven development, which aids rapid OS porting. By automating the porting process previously developed applications can be rapidly deployed in new systems with different, modified or new processors.